Prevalence of substance misuse among US veterans in the general population. (29th March 2017) - Hoggatt, Katherine J.; Lehavot, Keren; Krenek, Marketa; Schweizer, Catherine Amanda; Simpson, Tracy
Abstract : Background and Objectives: Epidemiologic data on substance misuse prevalence among US Veterans are crucial to plan for Veterans' future healthcare needs. We estimated US Veterans' age‐specific, overall, and age‐adjusted prevalence of substance misuse, assessed whether prevalence differed between Veterans and civilians, and examined temporal trends in prevalence. Methods: Substance‐related measures were obtained from the National Surveys on Drug Use and Health, 2002–2012 ( N = 24, 210 Veterans; 338, 556 civilians). Results: Among women and men Veterans overall, past‐month heavy episodic drinking and daily cigarette smoking were the most prevalent types of substance misuse. For Veteran women and men ages 18–25, the prevalence of past‐year illicit drug use was 29% and 38%, which was comparable to the prevalence of past‐month daily cigarette smoking, and the prevalence of past‐year prescription drug misuse was 14% and 18%. For men ages 18–25, heavy episodic drinking, daily cigarette smoking, alcohol use disorder (AUD), and substance use disorder were more prevalent among Veterans than civilians. For women, the age‐specific, overall, and age‐adjusted prevalence of daily cigarette smoking was generally greater among Veterans than civilians. There was a decreasing temporal trend in overall AUD prevalence among Veteran men, reflecting a decreasing trend in age‐specific prevalence among Veteran men ages 35–49. Discussion and Conclusions: Young Veterans' high prevalence of substance misuse, and the generally high prevalence of daily smoking among Veterans, underscore the need for evidence‐based assessments and treatment options that are accessible and effective for Veterans. Scientific Significance: This study provides foundational information on the epidemiology of substance misuse among Veterans. (Am J Addict 2017;26:357–365)